Human-Robot Interaction using Mixed Reality - Gallala, Abir; Hichri, Bassem; Plapper, Peter (2021 International Conference on Electrical, Computer and Energy Technologies (ICECET), 2021)
All along the appearance of the fourth industrial revolution many research and engineering fields has been facing a significant growing notably in robots. These interests evolve from the development of robots for structured industrial environments to collaborative and autonomous development operating in hybrid environments. Several problems have arisen with the growing number of collaborative robots; they are not user-friendly to work in hybrid teams and they also require high engineering and computational capabilities to program. Industry 4.0 has endorsed the combination of diverse new technologies that build-up a more efficient and user-friendly human-robot interaction such as Augmented and Mixed Reality, System integration, Internet of Things and 3D simulation. In this paper, we propose our approach which is a Mixed Reality-based human-robot interaction method for an human-friendly and easy cobot programming. The presented method is a marker-based algorithm that allows users to easily interact with cobot.